2019
DOI: 10.1021/acs.iecr.9b03296
|View full text |Cite
|
Sign up to set email alerts
|

Stereo-polymerization of 1,3-Butadiene by Cobalt Catalysts in the Presence of External Donor: Access to 1,2-Syndiotactic Polybutadiene with Tunable Properties

Abstract: Disulfide carbon (CS 2 ) and triphenyl phosphine (TPP) were tested as donors for cobalt (Co1, Co2, and Co3)catalyzed 1,2-syndiotactic polymerization of butadiene. With CS 2 , a 1,2-selectivity of 96.8% and syndiotacticity (rr) up to 97% were achieved by Co1−Co3/Al i Bu 3 /CS 2 , yielding highly crystallized polybutadiene resin. Variations on polymerization temperature (0−80 °C), catalyst loading, and polymerization time did not significantly affect the 1,2-incorporation and syndiotactic conformation of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The characteristic 1,2 regio‐selectivity can be interpreted assuming a cis ‐ η 4 ‐coordination for the monomer and an anti ‐ η 3 bond between the growing polymer chain and the iron ionic, as proposed by Natta et al and Ricci et al 2,42 It is conceivable that primary 1,2 regiochemistry of butadiene polymerization occurs by reaction of the new monomer to C3 of the last‐inserted allylic units 46,47 . The stereospecificity strongly depends reciprocal orientation of coordinated monomers and the allyic terminal, differing from non‐metallocene catalyst for propene polymerization 21,22 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The characteristic 1,2 regio‐selectivity can be interpreted assuming a cis ‐ η 4 ‐coordination for the monomer and an anti ‐ η 3 bond between the growing polymer chain and the iron ionic, as proposed by Natta et al and Ricci et al 2,42 It is conceivable that primary 1,2 regiochemistry of butadiene polymerization occurs by reaction of the new monomer to C3 of the last‐inserted allylic units 46,47 . The stereospecificity strongly depends reciprocal orientation of coordinated monomers and the allyic terminal, differing from non‐metallocene catalyst for propene polymerization 21,22 .…”
Section: Resultsmentioning
confidence: 91%
“…We have made great contribution to 1,2 stereoselective polymerization by iron catalyst with the aid of dialkyl(aromatic) hydrogen phosphites 37–39 and triarylphoshate as additive 40–42 . The phosphoryl moiety played significant role in stabilizing the active species and inducing 1,2 syndiotactic stereospecificity.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon disulfide (CS 2 ) has been proved to be an efficient stereo‐regulator in cobalt‐catalyzed catalyzed polymerization of butadiene 35–37 . It is interesting to find that catalytic performances are greatly influenced by adding of CS 2 as well.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon disulfide (CS 2 ) has been proved to be an efficient stereo-regulator in cobalt-catalyzed catalyzed polymerization of butadiene. [35][36][37] It is interesting to find that catalytic performances are greatly influenced by adding of CS 2 as well. The first set of reactions was performed by increasing progressively the amount of CS 2 in the presence of a fixed amount of MAO (entries 5-7, Table 2).…”
Section: Polymerization Of Isoprenementioning
confidence: 99%
“…[10][11][12] Metallocene catalysts have occupied a certain position in the polybutadiene market, 13,14 but in order to better control the polymer stereoregularity, people still devote a lot of effort to exploring Ziegler-Natta catalysts, including iron, cobalt, chromium, etc. [15][16][17] The Mo-based polybutadiene catalytic system has stable 1,2-stereoselectivity. It has been confirmed that changing the type and dosage of ligands or co-catalysts in the catalytic system fails to significantly change the polymer microstructure.…”
Section: Introductionmentioning
confidence: 99%